Information Management : a Systemic Model - Maria Manuela Gomes de Azevedo Pinto (2007)
The main purpose of this article is to present a case study, the project "Integrated Management of the Municipality Information System" applied to the current management of the City Council of Vila do Conde, which was developed under a new vision of the archives and the Archivistics, bringing possible the design of a new Information Management Model theoretically based in the Information Science. Reflecting the post-custodial, dynamical, informational and scientific paradigm, we want to fit the organizational needs related with the challenges set by the Information and Knowledge Society, the new vision of the public service and the relation between Government and citizens. If we consider the natural complexity of the producing structure's and the information system's analysis, essential to improve the changes and the modernization process, and the unquestionable emergency of the "digital information age", we can notice that we present here a period that enables simultaneously an analytical but also critical approach which is extremely necessary and shows the new role of the information professionals as information managers.